The Dynamics of Poverty and the Effectiveness of Poland's Safety Net (1993 96) - Okrasa, Włodzimierz (The World Bank, 1999)
November 1999 - Changes in Poland's family allowances and unemployment benefits have significant but different effects on different groups of households. In deciding on strategies to address long-term poverty, policymakers must take such differences into account. Okrasa analyzes how the incidence of household endowments and the allocation of social benefits affect families' transitions into and out of poverty. Using panel data for 1993-96 from Poland's Household Budget Survey, and a framework based on sample survival analysis techniques, Okrasa evaluates how various policies will affect households with specific characteristics that make them likely to become poor or to move out of poverty under different scenarios (including whether or not they receive a given amount of a particular type of social transfer). He also discusses how nonincome sources of welfare, such as savings, credits, and loans, affect the likelihood that families will become or stop being poor. He concludes that family allowances and unemployment benefits, the two major social programs analyzed, have significant but different effects on different groups of households (characterized in terms of the age, gender, marital status, and educational attainment of the head of household; the size, type, location, and sector of employment of the family or household; and the year in which the household fell into poverty). If the share of family allowances in total household income were reduced by 1 percent, for example, the average length of poverty would be increased by roughly 2 percent. But a 1 percent change in unemployment benefits would yield a 3 percent change in the average duration of poverty.